2020
DOI: 10.1007/s11096-020-01117-x
|View full text |Cite
|
Sign up to set email alerts
|

Size of the associations between anticholinergic burden tool scores and adverse outcomes in older patients

Abstract: Background Several anticholinergic scales and equations to evaluate the anticholinergic burden have been previously created. Association of these instruments with the anticholinergic outcomes are usually estimated by means of hypothesis contrast tests, which ignore the size of the association effect. Objective To evaluate the effect size of the associations between the scores on cumulative anticholinergic burden instruments with peripheral or central anticholinergic adverse outcomes in older patients. Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…The impact of the anticholinergic burden on nutrition may be explained by the gastrointestinal system and cognitive effects of anticholinergic agents (5). One of the well-known peripheral side effects, dry mouth (xerostomia), leads to poor dentition, altered taste, difficulty in deglutition, and digestion (34). Dysphagia makes the development of aspiration more likely and causes serious complications such as aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the anticholinergic burden on nutrition may be explained by the gastrointestinal system and cognitive effects of anticholinergic agents (5). One of the well-known peripheral side effects, dry mouth (xerostomia), leads to poor dentition, altered taste, difficulty in deglutition, and digestion (34). Dysphagia makes the development of aspiration more likely and causes serious complications such as aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the previous study on this topic has used measures of anticholinergic burden to determine the risk of delirium. Unfortunately, these scales have significant variability, 23 and in a systematic review, the association between delirium and anticholinergics varied based on the method used to calculate anticholinergic burden 10 . This likely contributes to some of the variability in the literature, and may account for clinical studies supporting a lack of association between anticholinergic medications and delirium 24 …”
Section: Discussionmentioning
confidence: 99%
“…The ADS presented a significant association with dry mouth in 2 studies [12,81] but not with constipation [12]. Lavrador et al [63] demonstrated that the ARS performed better than the ACB, ADS and DBI in predicting these peripheral negative outcomes, although the effect size was weak.…”
Section: Functional and Physical Outcomesmentioning
confidence: 99%
“…Initially, the minimum recommended daily dose was established according to approved US Food and Drug Administration (FDA) information. Further studies using the DBI established the British National Formulary as the gold standard for obtaining this information [63].…”
Section: Drug Burden Index (Dbi)mentioning
confidence: 99%
See 1 more Smart Citation